American football and other sports injuries may cause migraine/persistent pain decades later and can be treated successfully with electrical twitch-obtaining intramuscular stimulation (ETOIMS). Issue 2 (24th March 2017) - Chu, J; McNally, S; Bruyninckx, F; Neuhauser, D
Abstract : Introduction: Autonomous twitch elicitation at myofascial trigger points from spondylotic radiculopathies-induced denervation supersensitivity can provide favourable pain relief using electrical twitch-obtaining intramuscular stimulation (ETOIMS). Aim: To provide objective evidence that ETOIMS is safe and efficacious in migraine and persistent pain management due to decades-old injuries to head and spine from paediatric American football. Methods and materials: An 83-year-old mildly hypertensive patient with 25-year history of refractory migraine and persistent pain self-selected to regularly receive fee-for-service ETOIMS 2/week over 20 months. He had 180 sessions of ETOIMS. Pain levels, blood pressure (BP) and heart rate/pulse were recorded before and immediately after each treatment alongside highest level of clinically elicitable twitch forces/session, session duration and intervals between treatments. Twitch force grades recorded were from 1 to 5, grade 5 twitch force being strongest. Results: Initially, there was hypersensitivity to electrical stimulation with low stimulus parameters (500 µs pulse-width, 30 mA stimulus intensity, frequency 1.3 Hz). This resolved with gradual stimulus increments as tolerated during successive treatments. By treatment 27, autonomous twitches were noted. Spearman's correlation coefficients showed that pain levels are negatively related to twitch force, number of treatments, treatment session duration and directly related to BP and heart rate/pulse. Treatment numbers and session durations directly influence twitch force. At end of study, headaches and quality of life improved, hypertension resolved and antihypertensive medication had been discontinued. Conclusions: Using statistical process control methodology in an individual patient, we showed long-term safety and effectiveness of ETOIMS in simultaneous diagnosis, treatment, prognosis and prevention of migraine and persistent pain in real time obviating necessity for randomised controlled studies.